The speech act of commissive in the folkloric story “ڕەشکێ شەڤێ” - Yousif, Hazhar; Hassan, Rondik; Ameen, Pirzheen (Humanities Journal of University of Zakho, 2022)
The speech act of commissive is a type of verb mentioned by Searle in his classification of the speech acts. This research sheds light on the types of speech act of commissive in the “ڕەشکێ شەڤێ” folklore story. This research was conducted using the Searle model for analyzing the data statistical methods were used. One of the most important findings of this research is that the mentioned story includes all types of speech acts of commissive, which are (warning, promise, oath, threat, offer, clarification, and intimidation). The research consists of two chapters; the first chapter is devoted to Speech Verbs and Speech Verbs of commissive. The second chapter represents the applied chapter of the research and focuses on the application of speech verbs to the verb of commissive in the mentioned story.